Improving Volleyball Bottom Passing Skills Using Jigsaw Cooperative Model in Junior High School Students - Piranda, Muhammad Fiqih; Apriani, Leni; Alpen, Joni (Yayasan Insan Mulia Bima, 2025)
Lower passing in volleyball is a fundamental skill for students, yet many struggle to master it. This study aims to enhance lower passing skills using the Jigsaw cooperative learning model. The research employed Classroom Action Research (CAR) with two cycles. The participants were 29 students from Grade IX-3 at SMP Negeri 6 Siak Hulu, consisting of 16 male and 13 female students. Data were collected using observation sheets and lower passing skill tests. The analysis measured the percentage of students achieving mastery. The results showed a significant improvement in lower passing skills. In the first cycle, 58.62% of students met the mastery criteria. After refinements in the second cycle, the percentage increased to 96.55%, with 28 students reaching the Minimum Mastery Criteria (MMC). These findings confirm that the Jigsaw cooperative learning model enhances students' understanding of lower passing techniques, motivation, and participation. Future research could explore additional factors, such as training duration and variations in instructional strategies, to optimize the effectiveness of Jigsaw in sports education.